Dampak Media Pembelajaran Interaktif Articulate Storyline pada Pembelajaran Instalasi Tenaga Listrik - Sarah Yondrias; Ta'ali Ta'ali (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This study aims to determine the impact of interactive media on improving student learning outcomes and the percentage of completeness of learning outcomes after the application of Articulate Storyline interactive media in electrical power installation subjects at SMK Negeri 1 Mandau. The type of research used is experimental research with a One Group Pretest Posttest design, the subjects of this study were students of class XI TITL 1 SMK Negeri 1 Mandau in the 2023/2024 academic year consisting of 33 students. In this study, the data collection method used was the Pretest and Posttest questions which were validated by expert weighers, namely subject expert lectures and subject teachers. Before the treatment is given first given a pretest question (initial test) and after the treatment is given at the end of the learning be given a posttest question (final test). The results of the pretest (initial Test) show the value before the learning is given treatment and the result of the posttest (final test) show the value after the learning is given treatment. The result of this study indicates that the application of Articulate Storyline interactive learning media in the XI TITL class electrical power installation subject at SMK 1 Mandau has an impact on improving student learning outcomes. These results can be seen based on the realm of knowledge, namely, the result of the pretest and posttest analyzed using the Effect Size formula which falls into a very large category and using the percentage of completeness of learning outcomes increased from a very low category to very high. Thus the learning model using Articulate Storyline interactive media improves student learning outcomes in electrical power installation subjects.